2005
DOI: 10.1089/acm.2005.11.21
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy for Menopausal Symptoms in Breast Cancer Survivors: A Preliminary Randomized Controlled Trial

Abstract: Small sample size precludes definitive answers, but results from this preliminary trial suggest that homeopathy may be of value in the treatment of menopausal symptoms and improving quality of life, especially in those women not on tamoxifen. Larger studies should be carried out that also include healthy women who want to avoid hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 10 publications
0
52
0
6
Order By: Relevance
“…A total of 22 trials (54%) reported both sample size calculations and intention to treat analyses. Eight trials (20%) did not report sample size calculations or intention to treat analyses (53,57,60,61,64,67,68,73). Four of these studies also had a methodological quality of B (medium quality) (53,64,67,73).…”
Section: Methodological Quality Of the Rctsmentioning
confidence: 99%
“…A total of 22 trials (54%) reported both sample size calculations and intention to treat analyses. Eight trials (20%) did not report sample size calculations or intention to treat analyses (53,57,60,61,64,67,68,73). Four of these studies also had a methodological quality of B (medium quality) (53,64,67,73).…”
Section: Methodological Quality Of the Rctsmentioning
confidence: 99%
“…Even though the results were not positive for improving hot flushes, one cannot ignore a significant improvement in general health score that was observed in both homeopathy groups as compared with the placebo group. Researchers concluded that breast cancer survivors did have some positive benefit from the use of homeopathic remedies [25].…”
Section: Homeopathy Combined With Conventional Cancer Carementioning
confidence: 99%
“…Some homeopaths report significant clinical remissions and cures of the primary cancer disease process, 51 in addition to palliation of adjunctive symptoms from the disease and conventional cancer treatments such as radiotherapy and chemotherapy. [52][53][54] Mainstream researchers at the cutting edge of conventional medicine have explicitly recognized that cancer biology is complex and multifactorial. Systems biologists are grappling with the reality that different people can exhibit the same phenotype but arrive at the same "destination" via multiple different, multifactorial pathways.…”
Section: Systems Biology In Medicine and Cancer Research: A Bridge Tomentioning
confidence: 99%